Rancang Bangun Aplikasi E-Learning Berbasis Web Dengan Metode Agile Pada SMP SMK Bina Ikhwani - Muhammad Elang Hardifal; Nardiono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
SMP and SMK Bina Ikhwani are schools located on Jl. Cereme Rt.01 Rw.03 Sinarsari Hamlet, Dramaga District, Bogor Regency, West Java Province. Currently the learning process at Bina Ikhwani Middle School and Vocational School uses conventional methods and E-Learning as an online learning method. The conventional method is by carrying out face-to-face activities between teachers and students with textbooks as material in the process of teaching and learning activities in class, while for Bina Ikhwani Middle School and Vocational High School E-Learning they still use available platforms such as Google Classroom, WhatsApp, and email. SMP and SMK Bina Ikhwani need independent E-learning applications that are easier to condition. So in writing this thesis a website-based E-learning application was made to help the online learning process. The purpose of this study was to design and build an independent website-based E-Learning Application to improve online learning at Bina Ikhwani Vocational High School so that online learning can be maximized. This website was built using the Agile Extreme Programming method as a system development method. The PHP programming language, Laravel framework, MYSQL database as storage and software testing are carried out using the Blackbox Testing method. With the existence of a website-based E-learning application at Bina Ikhwani Middle School that has been built which is equipped with material management features, assignments, discussions, and grades can help make it easier for students and teachers in the online learning process.